O cinema, o tempo social e o seu intérprete - Tolentino, Célia Aparecida Ferreira [UNESP] (My University, 2013)
By understanding art as a particular form of knowledge is possible to think that sociology has much to learn from it. One thesis that we share in this essay is that the art is able to perform the synthesis of the historical time for its specifi c capacity to be in the world, because, while scientifi c knowledge search universal categories, intending to reduce as much the infl uence of human and social aspects in the apprehension of phenomena, aesthetic knowledge, even if it seeks abstract referentials, can not get rid of the experience and the world around it. This premise, based on the reading of Fredric Jameson, worth as much to the art authorial as for the one performed in series, this is, the production of the cultural industry. Both one and another, in their own way, translates the social time, task that fi ts to criticism unravel.

Entendendo a arte como uma forma particular de conhecimentoé possível pensar que a sociologia tem muito a aprender com ela. Uma das tesesque compartilhamos nesse ensaio é a de que a arte é capaz de realizar a síntesedo tempo histórico por sua capacidade específi ca de ser e estar do mundo, pois,enquanto o conhecimento científi co busca categorias universais, intentando reduzirao máximo a infl uência dos aspectos humanos e sociais na apreensão dos fenômenos,o conhecimento estético, ainda que busque referenciais abstratos, não pode livrar-seda experiência e do mundo ao seu redor. Essa premissa, tomando como base a leiturade Fredric Jameson, vale tanto para a arte autoral como para aquela feita em série, istoé, a produção da indústria cultural. Tanto uma quanto a outra, ao seu modo, traduzo tempo social, tarefa que cabe à crítica desvendar.
Keywords: cinema e pensamento social; cinema e crítica social; Cinema e Sociedade